Anti-Malarial Targeting and Dosing Practices among Health Workers at Lower Level Health Facilities in Uganda - Kakeeto, Stella; Wanzira, Humphrey; Kagambirwe Karyeija, Gerald; Kamya, Moses; Bukirwa, Hasifa (Health, 2014)
Health worker shortages remain a significant challenge to delivery of health care services globally. Moving tasks, where appropriate, to less specialized health workers is recommended by the World Health Organization as a strategy to address this challenge. However, this concept is feared to raise specific quality concerns. This research aimed at assessing the performance of health workers to correctly prescribe (target) appropriate antimalarial treatment. Methods: We conducted a cross sectional study at three public health centre IVs in Uganda, with varying malaria transmission intensities (Kihihi-low, Kasambya-medium and Nagongera-high). We categorized prescribers into two groups: specialized prescribers (doctors and clinical officers) and less specialized prescribers (nurses and midwives). At each site, 100 records of patients seen between September and November 2011 and prescribed an antimalarial were retrieved for each group of prescribers. Correctness of the antimalarial drug prescribed and dose given were assessed for each group and compared to the 2005 Uganda national malaria treatment guidelines which recommend Artemether Lumefantrine (AL) for treatment of uncomplicated malaria and Quinine for complicated malaria. Results: Findings of the study showed that specialized health workers were more likely to target correctly as compared to the less specialized health workers [OR = 1.49 (1.00 - 2.22), p = 0.046]. Appropriateness of dosing was higher among specialized prescribers compared to less specialized prescribers however this was not significant [OR = 1.58 0.77 - 3.25), p = 0.206]. Age of the participants, history of fever, diagnosis of malaria and prescription experience were not associated with correct targeting. Conclusion: This study shows that task shifting at the targeting level is not suitable; however, there is inadequate evidence to show that this also applies to anti-malarial dosing. Task shifting for the treatment of Malaria in Uganda should be investigated further using larger studies if it is to be considered as an option for solving the health worker shortages especially in regions with few specialized health workers but high malaria burden.
Keywords: Task Shifting; Anti-Malarial; Prescription; Dosing